I am Princess X - Priest, Cherie (Scholastic Inc., 2016)
After the death of her best friend Libby, sixteen-year-old May starts seeing signs that Libby is still alive. The signs are stickers and advertisements for a superhero that May and Libby invented called Princess X. As she investigates the origin of the Princess X signs, May gets closer to understanding the truth of what happened to Libby.